Discretionary disclosure, efficiency, and signal informativeness - Pae, Suil (Journal of Accounting and Economics, 2002)
This paper studies a competitive asset market characterized by an adverse selection problem. The analysis focuses on the link between the market participants’ productive activities and discretionary disclosures. While informed parties’ discretion over disclosure allows them to earn private gains, it leads to an inefficient allocation of resources. A more informative signal makes the informed parties better off, but reduces the uninformed parties’ welfare. Nonetheless, it improves the economy's allocative efficiency. The paper also shows that when the signal quality is endogenous, the informed parties over-invest in the signal informativeness relative to the level that maximizes social welfare.